The Impact of Large Scale Social Restrictions (PSBB) on The Stock Price of Service Companies on The Indonesia Stock Exchange - Fanny Monica Anakotta (Institute of Computer Science (IOCS), 2021)
This study aims to determine the impact of large – scale social restrictions (PSBB) on the stock price of service companies on the Indonesia Stock Exchange. This research is a quantitative research in which the data source used is secondary data obtained from the website: http www.idx.co.id. Data collection techniques are through documentation in the form of stock prices H-14 to H-1 before the implementation of PSBB and H +1 up to H + 14 when the PSBB is implemented. The share price used is the closing price. Hypothesis testing in this study used statistical analysis tools paired sample t-test. And based on the results of the hypothesis test, it is concluded that there is no significant difference in the stock prices of service companies listed on the Indonesia Stock Exchange before and when PSBB are enacted.